1996
DOI: 10.1021/ja953460e
|View full text |Cite
|
Sign up to set email alerts
|

The Macrobicyclic Cryptate Effect in the Gas Phase

Abstract: The alkali cation (Li+, Na+, K+, Rb+, and Cs+) binding properties of cryptands [2.1.1], [2.2.1], and [2.2.2] were investigated under solvent-free, gas-phase conditions using Fourier transform ion cyclotron resonance mass spectrometry. The alkali cations serve as size probes for the cryptand cavities. All three cryptands readily form 1:1 alkali cation complexes. Ligand−metal (2:1) complexes of [2.1.1] with K+, Rb+, and Cs+, and of [2.2.1] with Rb+ and Cs+ were observed, but no 2:1 complexes of [2.2.2] were seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 73 publications
0
31
0
Order By: Relevance
“…12 . In the literature 15 it is well known that Li is small enough to fit within the 15C5 cavity contrary to other alkali cations which are too large. The combination of Li salt and UV irradiation increases the coloration of solution (absorption of the open form) which is stable and does not thermally bleach under dark conditions at room temperature even after 30 days.…”
Section: Resultsmentioning
confidence: 99%
“…12 . In the literature 15 it is well known that Li is small enough to fit within the 15C5 cavity contrary to other alkali cations which are too large. The combination of Li salt and UV irradiation increases the coloration of solution (absorption of the open form) which is stable and does not thermally bleach under dark conditions at room temperature even after 30 days.…”
Section: Resultsmentioning
confidence: 99%
“…Chen and co-workers, using Fourier transform ion cyclotron resonance mass spectrometry, reported that a second ligand binding to the cryptand encapsulated ion is unlikely. [24] Molecular dynamics simulations by Wipff and co-workers [7,8] demonstrated that ion pairing between the complexed alkali metal and a counterion is more likely in acetonitrile than in water, and more likely with 18-crown-6 than with 222. While the nature of the anion can influence the stability of the complexes, the counterion was omitted in the calculations presented herein due to computational intractability and the aforementioned reasons.…”
mentioning
confidence: 99%
“…These reviews highlight a multitude of diverse systems and different analytical methods. Large biomolecular receptor/ligand systems, involving protein, peptide, oligonucleotide, enzyme and drug interactions [9][10][11][12][13][14][15][16][17], as well as polyether binding and encapsulation studies [18][19][20][21][22][23][24][25][26], are well represented in the literature. Noncovalent complex formation by small biomolecules in MS has also been investigated, but to a lesser extent.…”
Section: Methodological Backgroundmentioning
confidence: 99%